'This is like seeing a human body totally from a different angle' : experiences of South African cisgender partners in cisgender-trans* relationships - Theron, Liesl (Gender Studies, 2015)
To date, the knowledge available about cisgender-trans* couples and their experiences is located in the global North. Research situated in the interest of trans*, transgender and transsexual people's lives most often furthers scholars' understanding of gender. In my research, I employed strategies to look at the experiences of the cisgender partners of masculine identifying trans* persons, in order to learn more about gender Post-apartheid South Africa is a country that is vibrant with discussions in mainstream platforms about contemporary political and socio-economic matters, regularly framed in sexist approaches with clear patriarchal messages. How and where does the trans* masculine person find role models and what is that impact on the cisgender-trans* relationship? Bringing together literature from the global North and South Africa, I formed a theoretical framework that served as the context to support my research. As a feminist, I employ both feminist theory and transgender theory in my qualitative study. I interviewed fourteen cisgender partners of masculine identifying trans* persons. From the rich data, five themes emerged and were analysed through a content analysis approach.